Frasnian-Famennian boundary successions (Upper Devonian) of different depositional settings and correlation in South China: Multiple stratigraphic approaches - Daizhao Chen; Zhenghui Guo; Liyu Zhang; Hairuo Qing; Lei Liang; Huihong Liao; Mu Liu; Maurice E. Tucker (Earth-Science Reviews, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Airborne particles increase skin damage through photoinduced release of superoxide anion and hydroxyl radicals - Xiaotong Xu; Shuting Wei; Qing’e Shan; Chuncheng Chen; Sijin Liu; Juan Ma (Journal of Environmental Sciences, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Vehicular VOC speciation dynamics under China's progressive emission standards: Mechanistic drivers from real-time monitoring - Anqi Wang; Menglei Wang; Zibing Yuan; Xuehui Liu; Qing'e Sha (Journal of Cleaner Production, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Ride comfort degradation triggered by jet flow as ultra-high-speed trains enter tunnels - Xin-Yuan Liu; Si-Yuan Zhu; E Deng; Yi-Qing Ni (Tunnelling and Underground Space Technology, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

Variation in seedling growth, root exudates and rhizosphere microbial communities of two temperate tree species under fluctuating light and extreme drought - Lulu Xie; Yanmeng Yang; Jingran Ma; Jiaojiao Deng; Clément E. Gille; Ziliang Zhang; Meng Liu; Thomas Matthew Robson; Qing-Wei Wang (Plant and Soil, 2025)

Enhanced sulfamethoxazole (SMX) degradation by Shewanella oneidensis MR-1 via a microbially driven Fenton reaction - Qing-Jiahui Fan; Wei Li; Gen-Ji Yao; Zu-Hao Wang; Han Fu; Yong-Di Liu; Bruce E. Rittmann (Journal of Water Process Engineering, 2025)

Design and synthesis of uniform defective carbon nanosheets via CoAl-layered double hydroxide interlayer confinement for boosting peroxymonosulfate activation with highly efficient degradation of antibiotics contaminants - Qi-E. Zhang; Chu-Chu Hu; Si-Qin Guo; Jia-Wei Liu; Si-Cheng Hu; Yong-Xin Xin; Jin-Gang Yu; Guo-Qing Zhao; Limin Lu (Journal of Environmental Chemical Engineering, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Storage temperature affects metabolism of sweet corn - Shiyu Liu; Xinyuan Zhou; Yunxiang Wang; Qing Wang; Lili Ma; Cai’e Wu; Ronghuan Wang; Yaxing Shi; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2025)

Effects of rumen metabolite butyric acid on bovine skeletal muscle satellite cells proliferation, apoptosis and transcriptional states during myogenic differentiation - Xiao-Wei Wang; Yan-Ling Ding; Cheng-Long Li; Qing Ma; Yuan-Gang Shi; George E Liu; Cong-Jun Li; Xiao-Long Kang (Domestic Animal Endocrinology, 2025)

Influence of land-use type on earthworm diversity and distribution in Yunnan: Insights from soil properties - Chang-E Liu; Qing-Rui Luo; Yan-Lan Xiao; Hong-Yang Li; Hong-Juan Dong; Chang-Qun Duan (Applied Soil Ecology, 2025)

Reproducing the flight behavior of falling debris from railway tunnel vault using a high-speed train ejection experiment and moving-overset-mesh simulation - E Deng; Yi-Kang Liu; Wei-Chao Yang; Yi-Qing Ni (Tunnelling and Underground Space Technology, 2024)

Chlorine dioxide affects metabolism of harvested sweet corn - Shiyu Liu; Yanyan Zheng; Ronghuan Wang; Yaxing Shi; Wantao Cai; Tianjun Xu; Cai’e Wu; Lili Ma; Chunmei Bai; Xinyuan Zhou; Qing Wang; Christopher B. Watkins; et al. (Postharvest Biology and Technology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

New 4',5'-methylenedioxyflavone derivatives from the whole plant of sarcandra glabra - Ya-Qiu Qin; Wei Liu; Rui Yin; Ping-Ting Xiao; Zi-Yuan Wang; Tian-Qing Huang; E-Hu Liu (Natural Product Research, 2024)

Stress ratio sensitivity—a novel parameter for evaluating the shearing-based structural characteristic of loess - Meng Yao; Hui-e Chen; Hui Li; Qing wang; Yan Han; Qingbo Yu; Yibo Liu (Bulletin of Engineering Geology and the Environment, 2024)

Dust diffusion laws during partition excavation by boom-type roadheader in a metro tunnel - Ning Liu; Xiong Wu; E Deng; Yi-Qing Ni; Wei-Chao Yang; Guo-Zhi Li (Tunnelling and Underground Space Technology, 2023)

Aerodynamic behavior of flaky spalled blocks in high-speed rail tunnel lining under slipstream - Wei-Chao Yang; Jia-Bao Yang; E Deng; Yi-Qing Ni; Yi-Kang Liu (Tunnelling and Underground Space Technology, 2023)

Direct identification of total and missing OH reactivities from light-duty gasoline vehicle exhaust in China based on LP-LIF measurement - Xuehui Liu; Zibing Yuan; Qing'e Sha; Shengrong Lou; Hongli Wang; Xin Li; Junyu Zheng; Bin Yuan; Min Shao (Journal of Environmental Sciences, 2023)

Aerodynamic intensification effect and dynamic response of cracks on high-speed railway tunnel linings - Yi-Kang Liu; E. Deng; Wei-Chao Yang; Yi-Qing Ni; Zhong Zhou; Jun-Jie Zhang (Tunnelling and Underground Space Technology, 2023)

Assessing the co-benefits of emission reduction measures in transportation sector: A case study in Guangdong, China - Mingming Hu; Qing'’e Sha; Guanglin Jia; Yingying Liu; Yan You; Junyu Zheng (Urban Climate, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Neuroprotective carbazole alkaloids from Streptomyces sp. HS-NF-1322 by inhibition of ferroptosis - Yuan Peng; Yi-Tong Luo; Qian-Qing Liu; Si-Qing Lou; Dong-E. Liang; Zha-Jun Zhan; Zhi-Fang Xi; Lie-Feng Ma (Phytochemistry Letters, 2023)

A coupling analysis method of foundation soil dynamic responses induced by metro train based on PDEM and stochastic field theory - E Deng; Xin-Yuan Liu; Yi-Qing Ni; You-Wu Wang; Chen-Yang Zhao (Computers and Geotechnics, 2023)

An interaction of inorganic arsenic exposure with body weight and composition on type 2 diabetes indicators in Diversity Outbred mice - James G. Xenakis; Christelle Douillet; Timothy A. Bell; Pablo Hock; Joseph Farrington; Tianyi Liu; Caroline E. Y. Murphy; Avani Saraswatula; Ginger D. Shaw; Gustavo Nativio; Qing Shi; Abhishek Venkatratnam; et al. (Mammalian Genome, 2022)

Electrospun nanofibers food packaging: trends and applications in food systems - Dur E. Sameen; Saeed Ahmed; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Qing Zhang; Suqing Li; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Impact of ambient temperature on life loss per death from cardiovascular diseases: a multicenter study in central China - Ling-Shuang Lv; Chun-Liang Zhou; Dong-Hui Jin; Wen-Jun Ma; Tao Liu; Yi-Jun Xie; Yi-Qing Xu; Xing-E Zhang (Environmental Science and Pollution Research, 2022)
Background In the context of global climate change, studies have focused on the ambient temperature and mortality of cardiovascular diseases (CVDs). However, little is known about the effect of ambient temperature on year of life lost (YLL), especially the life loss per death caused by ambient temperature. In this study, we aimed to assess the relationship between ambient temperature and life loss and estimate the impact of ambient temperature on life loss per death. Methods We collected daily time series of mortality and meteorological data from 70 locations in Hunan province, central China, in periods ranging from Jan. 1, 2013, to Dec. 31, 2017. Crude rates of YLL were calculated per 100,000 people per year (YLL/100,000 population) for each location. A distributed lag nonlinear model and multivariate meta-regression were used to estimate the associations between ambient temperature and YLL rates. Then, the average life loss per death attributable to ambient temperature was calculated. Results There were 711,484 CVD deaths recorded within the study period. The exposure-response curve between ambient temperature and YLL rates was inverted J or U-shaped. Relative to the minimum YLL rate temperature, the life loss risk of extreme cold temperature lasted for 10 to 12 days, whereas the risk of extreme hot temperature appeared immediately and lasted for 3 days. On average, the life loss per death attributable to non-optimum ambient temperatures was 1.89 (95% CI, 1.21-2.56) years. Life loss was mainly caused by cold temperature (1.13, 95% CI, 0.89‑1.37), particularly moderate cold (1.00, 95% CI, 0.78‑1.23). For demographic characteristics, the mean life loss per death was relatively higher for males (2.07, 95% CI, 1.44‑2.68) and younger populations (3.72, 95% CI, 2.06‑5.46) than for females (1.88, 95% CI, 1.21-2.57) and elderly people (1.69, 95% CI, 1.28-2.10), respectively. Conclusions We found that both cold and hot temperatures significantly aggravated premature death from CVDs. Our results indicated that the whole range of effects of ambient temperature on CVDs should be given attention.

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

Attenuated Reactive Gliosis and Enhanced Functional Recovery Following Spinal Cord Injury in Null Mutant Mice of Platelet-Activating Factor Receptor - Yuanyi Wang; Zhongwen Gao; Yiping Zhang; Shi-Qing Feng; Yulong Liu; Lisa B. E. Shields; Ying-Zheng Zhao; Qingsan Zhu; David Gozal; Christopher B. Shields; Jun Cai (Molecular Neurobiology, 2016)

Over-expression of a WRKY transcription factor gene BoWRKY6 enhances resistance to downy mildew in transgenic broccoli plants - Ming Jiang; Qing-e Liu; Zhen-Ning Liu; Jin-Zhi Li; Cai-Ming He (Australasian Plant Pathology, 2016)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Analysis of air quality variability in Shanghai using AOD and API data in the recent decade - Qing Zhao; Wei Gao; Weining Xiang; Runhe Shi; Chaoshun Liu; Tianyong Zhai; Hung-lung Allen Huang; Liam E. Gumley; Kathleen Strabala (Frontiers of Earth Science, 2013)

Investigation of transferability of BovineSNP50 BeadChip from cattle to water buffalo for genome wide association study - Jun Jing Wu; Li Jun Song; Fang Jie Wu; Xian Wei Liang; Bing Zhuang Yang; D. Claire Wathes; Geoff E. Pollott; Zhangrui Cheng; De Shun Shi; Qing You Liu; Li Guo Yang; Shu Jun Zhang (Molecular Biology Reports, 2013)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)